Donor T-Cell Repertoire Profiling in Recipient Lymphoid and Parenchyma Organs Reveals GVHD Pathogenesis at Clonal Levels After Bone Marrow Transplantation in Mice - Wu, Yongxia; Fu, Jianing; Wang, Haizhen; Yu, Xue-Zhong (Frontiers in Immunology, 2021)
The diversity and composition of T-cell receptor (TCR) repertoire, which is the result of V, (D) and J gene recombination in TCR gene locus, has been found to implicate in T-cell responses in autoimmunity, cancer and organ transplantation. The correlation of T-cell repertoire with the pathogenesis of graft-versus-host disease (GVHD) after allogeneic hematopoietic cell transplantation remains largely undefined. Here, by utilizing high-throughput sequencing of the genes encoding TCRβ-chain, we comprehensively analyzed profile of T-cell repertoire in recipient lymphoid and GVHD target organs after bone marrow transplantation (BMT) in mice. In lymphoid organs, TCR diversity was narrowed accompanied with reduced numbers of unique clones while increased accumulation of dominant clones in allogeneic T cells compared to syngeneic T cells. In individual allogeneic recipient, donor-derived TCR clones were highly overlapped among tissue sites, and the degree of overlapping was increasing from day 7 to 14 after allogeneic BMT. The top clones in peripheral blood, gut, liver and lungs were highly mutually shared in an allogenic recipient, indicating blood has the potential to predict dominant clones in these GVHD target organs. T cells in GVHD target organs from allogeneic recipients had fewer overlapped clones with pre-transplant donor T cells compared to those from syngeneic recipients. Importantly, the top 10 clones in allogeneic recipients could not be traced back in pre-transplant donor T cells, indicating clonal expansion of de novel generated rearrangements. Interestingly, even started from same pool of donor repertoires, T cells had very few overlapped clones between each allogeneic recipient who developed completely different dominant clones. We were only able to trace a single clone shared by 3 replicate allogeneic recipients within the top-500 clones. Although dominant clones were different among allogeneic recipients, V26 genes were consistently used more frequently by TCR clones in allogeneic than syngeneic recipients. This is the first study to extensively examined the feature of T-cell repertoire in multiple lymphoid and parenchyma organs, which establishes the association between T-cell activation and GVHD pathogenesis at the level of TCR clones. Immune repertoire sequencing-based methods may represent a novel personalized strategy to guide diagnosis and therapy in GVHD.